2009
DOI: 10.1074/jbc.m109.014811
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factors β Coordinate Cartilage and Tendon Differentiation in the Developing Limb Mesenchyme

Abstract: Transforming growth factor ␤ (TGF␤) signaling has an increasing interest in regenerative medicine as a potential tool to repair cartilages, however the chondrogenic effect of this pathway in developing systems is controversial. Here we have analyzed the function of TGF␤ signaling in the differentiation of the developing limb mesoderm in vivo and in high density micromass cultures. In these systems highest signaling activity corresponded with cells at stages preceding overt chondrocyte differentiation. Interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
179
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(197 citation statements)
references
References 71 publications
17
179
1
Order By: Relevance
“…The BMP inhibitor Noggin represses the expression of Sox9 while inducing the Scx expression [35]. In micromass cultures of undifferentiated mesodermal cells, TGF-β/Smad signaling is a direct inducer of Sox9 and Scx, but transcriptional repressors of TGF-β signaling (Tgif1 and SnoN) modulate the expression of Sox9 and Scx [36]. These findings suggest that TGF-β superfamily modulate the balance between Sox9 and Scx according to each differentiation stage of chondrogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The BMP inhibitor Noggin represses the expression of Sox9 while inducing the Scx expression [35]. In micromass cultures of undifferentiated mesodermal cells, TGF-β/Smad signaling is a direct inducer of Sox9 and Scx, but transcriptional repressors of TGF-β signaling (Tgif1 and SnoN) modulate the expression of Sox9 and Scx [36]. These findings suggest that TGF-β superfamily modulate the balance between Sox9 and Scx according to each differentiation stage of chondrogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The transforming growth factor (TGF-b) signaling through SMAD-2/3 downstream effectors has an increasing interest in regenerative medicine and lineage specification during human embryonic development [15,16]. In contrast to specific bone morphogenic proteins (BMPs), which are known to play an important role in directing cell fate decisions toward mesoderm and further differentiation into MSCs, the mesodermal effects of TGF-b signaling in human embryonic development is controversial [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…4 Multiple studies have shown that TGF-b is up-regulated after tendon injury [5][6][7] and after their injection into the injured tendon, pluripotent equine embryo-derived stem cells (ESCs) express SCX. 5 The addition of TGF-b3 induces tenogenic differentiation of in vitro cultures of mesenchymal stem cells (MSCs), 8 micromass cultures of undifferentiated limb mesenchyme, 9 and equine ESCs. 5 Taken together, this suggests that TGF-b signaling plays a key role in triggering the initiation of tenocyte differentiation from stem cells and tendon progenitors.…”
Section: Introductionmentioning
confidence: 99%